ChemInform Abstract: Fluoroform‐Derived CuCF3 for Low‐Cost, Simple, Efficient, and Safe Trifluoromethylation of Aryl Boronic Acids in Air. Issue 3 (22nd January 2013) - Novak, Petr; Lishchynskyi, Anton; Grushin, Vladimir V.
Abstract The reaction is effective for aromatic and heteroaromatic boronic acids and is not sensitive to electronic and steric effects.